Sedimentary study of coastal marine sediments near the estuaries of Al-Ghamqa and Al-Khawabi Rivers (Latakia University Journal -Basic Sciences Series, 2020)
The Syrian coast lacks studies on the nature of sediments and the mechanism of their distribution. The study of sediments is important to understand sediment transportations and deposition, the identification of different sedimentation environments and the impact of transport dynamics in the form of sedimentary grains. Twenty-five sedimentary samples were collected from the coastal area during summer and winter to determine the nature and distribution of sediments. The results of the granular analysis of the studied samples showed complete sand control with a small percentage of silt and a complete absence of clay. The results showed that the sediments were of average granular size, with good moderate sorting, very negatively skewed, and finally mesokurtic. These data indicate that sedimentation occurred under the influence of moderate to high-energy conditions due to the movement of currents and waves.